Moderating Effect of Illiquidity on The Relationship Between Momentum and Equity Returns in The Kenyan Capital Markets - Peter Kamau Ndichu; Robert Kisavi Mule (European Scientific Journal, ESJ, 2021)
This paper sought to examine the moderating effect of illiquidity on the relationship between momentum and equity returns in the Kenyan capital markets. Previous studies have shown that illiquidity has a time-varying effect on momentum strategies, but little is known whether illiquidity has a moderating effect on the relationship between momentum and equity returns in Kenyan capital markets. A longitudinal research design was used for this study to examine the causal inference. Data comprised of monthly transactions on the 20 equities used in the formulation of the NSE 20 share index over the period between Jan 2009 and up to March 2018 which formed 111 data points. ADF and PP results showed that Returns and momentum are stationary at levels while illiquidity was stationary at first difference. The error correction term was negative and statistically significant with or without the moderator. Results indicate that without a moderator percentage increase in momentum is linked to a 0.0000313% increase in returns in the short run. The study further shows that the effect of momentum on equity returns is moderated by illiquidity using a t-test. R2 changed from 0.427 to 0.4337 indicating a change of 0.006 at 0.05% significant level suggesting that illiquidity moderates the relationship between momentum and equity returns in the Kenyan capital markets.